Use of Reamed Interlocking Nail in the Management of Closed Tibial Shaft Fractures - Syed Ali Haziq Bukhari, Awais Ghulam Nabi, Muhammad Saad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Reamed interlocking nails are being tested for their ability to treat closed tibial shaft fractures. Study Design: Observational / Descriptive study Place and Duration: THQ kotmomin district Sargodha ,Punjab medical college. Jan 2021-Oct 2021 Methods: For this research, a total of 110 patients of both sexes participated. Cases were enrolled between the ages of 18 and 75. After obtaining written permission, demographic information about enrolled patients was collected. Patients with a reaming interlocking nail on their tibial shaft were brought to the emergency room. Union time and the incidence of complications were evaluated postoperatively. During the course of 12 months, all of the patients' follow-ups were completed. SPSS 23.0 was used to analyze the data. Results: The patients' average age was 30.12±6.33 years, and their BMI was 25.21±6.55 kg/m2. Majority cases 70 (63.6%) were male and 40 (36.4%) were female. The most prevalent cause of fracture was a car collision, followed by a fall from a great height. We found majority of the cases had tibial fracture at middle one third 77 (70%). Simple fractures had a mean union time of 11.32±9.54 weeks, whereas segmental fractures had a mean union time of 17.7±8.54 weeks. Union fractures occurred at a rate of 90 (81.8%), and overall satisfaction was 95 (86.4%). Conclusion: In this research, we came to the conclusion that the use of a reamed interlocking nail was the most successful and safest approach of treating closed tibial shaft fracture. In this research, the overall union rate was high, and there was minimal morbidity among the patients.